2021
DOI: 10.1177/00207640211003121
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety, depression, and psychological distress among the general population during the COVID-19 pandemic: A systematic review and meta-analysis

Abstract: Background: The COVID-19 pandemic is a worldwide epidemic declared by the world health organization as a public health emergency of concern and consequently inducing huge mental health and psychological reactions. Aims: This study is aimed to summarize the existing data regarding anxiety, depression, and psychological distress during the covid-19 pandemic among the wider population so that effective intervention strategies will be initiated. Methods: Pieces of literature that assessed anxiety, depression, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
160
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(168 citation statements)
references
References 63 publications
(198 reference statements)
3
160
0
5
Order By: Relevance
“…Regarding the lack of changes in perceived anxiety levels (as measured with the DASS_21), although we observed a decrease from the baseline to post-intervention, we also measured a slight increase in scores from the waiting period to the start of the protocol. This slight increase in the perceived anxiety from the control period to the start of the treatment could be explained by data reviewed by recent meta-analyses indicating a high prevalence (23.4%) of anxiety symptoms among the general population measured with the DASS-21 scale during the COVID-19 pandemic [84]. Additionally, we did not observe any effect of the intervention on the subjective perception of hopelessness.…”
Section: Discussionsupporting
confidence: 42%
“…Regarding the lack of changes in perceived anxiety levels (as measured with the DASS_21), although we observed a decrease from the baseline to post-intervention, we also measured a slight increase in scores from the waiting period to the start of the protocol. This slight increase in the perceived anxiety from the control period to the start of the treatment could be explained by data reviewed by recent meta-analyses indicating a high prevalence (23.4%) of anxiety symptoms among the general population measured with the DASS-21 scale during the COVID-19 pandemic [84]. Additionally, we did not observe any effect of the intervention on the subjective perception of hopelessness.…”
Section: Discussionsupporting
confidence: 42%
“…Its side effects have gradually started attracting people's attention. Psychological distress such as anxiety and depression have shown widespread occurrence in the global pandemic of COVID-19 ( 1 , 4 ). Our previous research has proved that in the second wave of the epidemic, quarantine can increase the anxiety levels of the population ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the outbreak and the measures to contain it are having a great impact on general population worldwide. Uncertainty, loss of control, isolation, and worries about one’s own health and that of beloved ones often lead to mental health issues and psychological distress [ 79 , 80 , 81 ]. Previous research showed that emerging adults are very prone to experience psychological distress during the current pandemic, and they could be considered as a vulnerable group [ 82 , 83 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%